Long-term rain attenuation probability and site diversity gain prediction formulas - Al-Tabatabaie, Kusay Faisal A. (2007)
The increasing growth of wireless communication systems has caused the usage of higher frequencies in order to have wider bands. However the increase of frequency will lead to the degradation of satellite communication performance. Rain attenuation is one of the most fundamental reasons of the degrading quality of services. Thus fade mitigation techniques will be used in order to compensate for excessive attenuation such as diversity protection schemes, power control and adaptive processing techniques. Among these techniques the most efficient is site diversity (SD). The aim of this project is to determine the effect of SD under the rain conditions, combine both categories for the estimation of slant path rain attenuation and SD gain. It includes the designing of algorithm flow which incorporated into MATLAB programming software. Also, the SD gain calculation in Skudai – Malaysia is included too. It is hoped that with the availability of data, the design process of fade mitigation techniques is greatly simplified. The ITU-R study Group 3 database is used in this project.